2011
DOI: 10.1108/ijsms-12-04-2011-b005
|View full text |Cite
|
Sign up to set email alerts
|

A service quality framework in the context of professional football in Greece

Abstract: As business environments of professional sport leagues become more highly complicated and unpredictable, the adaptation of effective marketing strategies and management principles is more important than ever for sports organisations. In particular, delivering a high quality service to the fans is critical as it influences revenues and the long-term viability of the organisation.Previous studies support that the provision of high quality services is critical in attracting spectators to the stadium, building spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 50 publications
1
30
0
3
Order By: Relevance
“…Evaluating effects of fan service quality on fan lifetime value constructs show that the domain service quality is significantly relationship to all four fan lifetime value constructs; Consumption Quantity (Beta= 0.188), word of mouth (Beta= 0.419), Media Usage (Beta= 0.259) and Attend intentions (B= 0.335). This finding is in line with the previous research in various areas suggesting that service quality is an essential variable for attracting and satisfied customers and it is a significant predictor of various consumer behavior variables such as cooperation, word of mouth, and purchasing (Choi , 2001;Theodorakis et al, 2011;Hill & Green, 2000;Westerbeek, 2000;Liu, 2008;Ko & Pastore, 2004). In this line, Davis (2008) has indicated that attendance is influenced by winning games and the quality of games.…”
Section: Discussionsupporting
confidence: 90%
“…Evaluating effects of fan service quality on fan lifetime value constructs show that the domain service quality is significantly relationship to all four fan lifetime value constructs; Consumption Quantity (Beta= 0.188), word of mouth (Beta= 0.419), Media Usage (Beta= 0.259) and Attend intentions (B= 0.335). This finding is in line with the previous research in various areas suggesting that service quality is an essential variable for attracting and satisfied customers and it is a significant predictor of various consumer behavior variables such as cooperation, word of mouth, and purchasing (Choi , 2001;Theodorakis et al, 2011;Hill & Green, 2000;Westerbeek, 2000;Liu, 2008;Ko & Pastore, 2004). In this line, Davis (2008) has indicated that attendance is influenced by winning games and the quality of games.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies have found that perceived quality has a positive effect on satisfaction with a sponsored event, customer satisfaction, brand commitment, and brand loyalty (An & Noh, 2009;Jeong, Ryu, & Brown, 2018;Koo et al, 2009;Lim, 2017;Theodorakis, Alexandris, & Ko, 2011). Perceived quality should lead consumers to trust and identify with a brand.…”
Section: B Hypothesesmentioning
confidence: 99%
“…Others have focused on the cognitive, emotional, and behavioral impacts of sponsorship (Chavanat, Martinent, & Ferrand, 2009;Gwinner & Bennett, 2008;Koo et al, 2006). Still others have focused on linking predeterminant factors (e.g., brand image, perception, and perceived quality) pertaining to sponsoring brands to satisfaction with sports events, customer satisfaction, commitment, and brand loyalty (An & Noh, 2009;Chen et al, 2012;Theodorakis, Alexandris, & Ko, 2011).…”
Section: ⅱ Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Particular attention is paid to the difference of sports based on participation and aimed at spectators by the nature of the customers’ role (active or passive) (Theodorakis and Alexandris, 2008). Some interventions have been made in spectator sports in order to measure the service quality (Ko et al, 2011; Theodorakis et al, 2011). Ko et al (2011) developed the “Model of Event Quality for Spectator Sport ” (MEQSS) and the “Scale of Event Quality for Spectator Sport” (SEQSS), which were specifically designed to evaluate the quality perceptions of spectators concerning the event.…”
Section: Introductionmentioning
confidence: 99%